2014
DOI: 10.1620/tjem.233.295
|View full text |Cite
|
Sign up to set email alerts
|

Residual Urinary Volume Is a Predictor of Overhydration in Patients on Peritoneal Dialysis

Abstract: Fluid overload is linked to hypertension and cardiovascular diseases in patients on peritoneal dialysis (PD). It is important to monitor the residual urinary volume in patients with end-stage renal disease (ESRD). In fact, fluid overload and residual urinary volume have been considered the risk factors of mortality in ESRD patients on PD. However, the relationship between residual urinary volume and fluid overload was still controversial. Therefore, the objective of this cross-sectional study was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
3
2
0
Order By: Relevance
“…One potential explanation is that UV has a stronger association with volume status. Several studies also revealed that extracellular volume expansion was associated with UV in patients on dialysis (27,32). Recently, overhydration measured by the Body Composition Monitor significantly correlated with UV but did not correlate with GFR-24U in patients on PD (27), supporting our observation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…One potential explanation is that UV has a stronger association with volume status. Several studies also revealed that extracellular volume expansion was associated with UV in patients on dialysis (27,32). Recently, overhydration measured by the Body Composition Monitor significantly correlated with UV but did not correlate with GFR-24U in patients on PD (27), supporting our observation.…”
Section: Discussionsupporting
confidence: 84%
“…Several studies also revealed that extracellular volume expansion was associated with UV in patients on dialysis (27,32). Recently, overhydration measured by the Body Composition Monitor significantly correlated with UV but did not correlate with GFR-24U in patients on PD (27), supporting our observation. In patients on HD, UV was the largest in patients with low interdialytic weight gain (interdialytic weight gain/dry weight ,1.0%), despite comparable GFR-24U (33).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…20,21 It is likely that residual urinary volume is the main predictor of overhydration in patients on PD. 22 Moreover, our study demonstrated a significant correlation between residual urine output and hydration status (r = −0.36; p = 0.004).…”
Section: Discussionsupporting
confidence: 50%
“…All of our subjects were non-anuric, with residual urine volume > 500 mL/day at baseline. One recent report (27) found that residual urine volume is the strongest predictor of volume overload in PD. Most of the subjects in both groups were taking diuretics prior to the study.…”
Section: Discussionmentioning
confidence: 99%